The Spatiality of Women’s Struggle within Porto’s Residents’ Movement during Portuguese Revolutionary Process (1974-75) - Ruivo Pereira, Catarina (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
This paper explores the role of women’s struggle within residents’ movements in the production and transformation of space in Porto during the PREC (the Portuguese Revolutionary Process of 1974-1976), analysing the spaces where these movements started, the issues they focused on, and how it related and acted within explicit and implicit views of family and gender relations in institutional approaches to housing development. It also considers how these were mirrored in housing policy options and design paradigms. In this way, by shifting the focus to women’s struggle at the grassroots, looking at those who were both the recipients of houses and actors of an ongoing struggle, this research explores the intersection between class and gender in the processes of housing and urban development.
Keywords: Popular Movements; Organised Women; Public Housing; Participatory Architecture; Feminist Practices